Empowerment of Health Habitus in The Host of Fruit Vegetable Sellers in Fending Off Covid-19 - Munthe, Hadriana Marhaeni; Trimurni , Februati; Lase, Eko Jono (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2021)
The implementation of this community service is directed at addressing the problem of inang-inang the fruit vegetable traders during the Covid-19 pandemic in Sembada traditional market, Titi Rantei sub-district. The health behavior habitus of this group refers to the condition o an attitude of disobdience or at least a lack of concern for public policies related to preventing spread of Covid-19. As a strategic group in the context o social relations both in private and domestic space, this group is alleged to have a dangerous impact on various parties. They have a potential to became carrier and local transmitter that endanger themselves and those closest to them and others. This service activitiy is carried out using methods including FGD, dialogue, puclic discussion, training and mentoring. The result of this service activity is in the form of a strong health against Covid-19 which refers to an obedient attitude to health protocol such as wearing masks, maintaining distance and washing hands. This group expected to become a role model as well as the front guard in stimulating the community to implement health protocols.